Fear of crime in residential areas / Siti Rasidah Md Sakip, Aldrin Abdullah and Mohd Najib Mohd Salleh - Abdullah, Aldrin; Mohd Salleh, Mohd Najib; Md Sakip, Siti Rasidah (Faculty of Architecture, Planning and Surveying, 2013)
Physical environmental elements such as gated elements are believed to have an effect towards the reduction of fear of crime in residential neighbourhoods. In Malaysia, the typical form of residences is that involving gated individual houses, while residences without gated elements are relatively a new development concept. Therefore, a survey on fear of crime among residents in housing areas with gated and non-gated residences was conducted in Bandar Baru Bangi, Selangor and Precinct 9B, Putrajaya. This research discovered that respondents inhabiting a gated residential area exhibit a higher fear of crime level (M=5.84, SD=1.23) when compared to respondents living in a non-gated residential area (M=3.85, SD=1.66).